Upaya Meningkatkan Hasil Belajar Ipa Melalui Model Pembelajaran Demonstrasi Pada Siswa Sekolah Dasar - ENDARNIATI, ENDARNIATI (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2018)
Whether by using Demonstration method can improve the learning achievement of fourth grade students of State Elementary School 002 Penghidupan Kampar District. The method used in this research is Classroom Action Research (PTK). This TOD uses demonstration learning methods. PTK consists of 5 stages: planning, action, observation, reflection. The results showed: (1) By using the demonstration learning, student learning outcomes of each cycle have increased significantly. Student learning outcomes in the first cycle meeting of 80 with 95% completeness, cycle II of 86 with 100% completeness. (2) Classical learning in the first cycle of 78.61% increased to 91.39% in cycle II and group learning from cycle I was 81.25% increased significantly in cycle II to 100%